2006
DOI: 10.1080/09723757.2006.11885977
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of the Alcohol Dehydrogenase Genes among the 28 Caste and Tribal Populations of India

Abstract: We report single nucleotide polymorphisms (SNPs) at the four sites in ADH2 and ADH3 genes among the 28 populations from southern parts of Andhra Pradesh, India. A total of 1048 individuals belonging to 28 endogamous populations distributed in the contiguous areas of the 6 southernmost districts of Andhra Pradesh were enrolled for the present study. Genotyping involved PCR and sequencing. We sequenced exon 3 and 9 of ADH2 and exon 8 of ADH3, besides the ADH2 3'UTR-rs17033 (72 bases down stream of ADH2 Arg369Cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Genetic studies conducted with 28 castes and tribal groups in India have also empirically demonstrated a genetic adaptation to withstand the intoxicant effects of drinking. This is possibly due to the complete absence of African specific ADH2*3 allele in the Indian population (Reddy et al, 2006). This study's findings reveal that married people are more likely to report alcohol use-related problems than unmarried respondents.…”
Section: Discussionmentioning
confidence: 67%
“…Genetic studies conducted with 28 castes and tribal groups in India have also empirically demonstrated a genetic adaptation to withstand the intoxicant effects of drinking. This is possibly due to the complete absence of African specific ADH2*3 allele in the Indian population (Reddy et al, 2006). This study's findings reveal that married people are more likely to report alcohol use-related problems than unmarried respondents.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, secondary esters are preferable compared with primary or tertiary esters, which are metabolically stable. Fourth, secondary alcohols are metabolized by isoforms of ADH that are not subject to genetic variability . In contrast, primary alcohols (eg, ethanol) are metabolized by an ADH isoform that has large genetic variation.…”
Section: Methodsmentioning
confidence: 99%